Influence of Ideological and Neurological Factors on Ethical Leadership Behavior: Evidence from Pakistan - Shamim, Nuzhat; Hasan, Shazai; Raja, Ahtesham Ali (International Journal of Psychosocial Rehabilitation, 2020)
The research was based on two theories moral self and ethical position theory to measure the ideological and neurological influences on the ethical behavior of leaders and was conducted in Pakistan. For the measurement of (bDMN) a neurological test EEG was proposed to be calculated and LORETA software to be used to interpret the brain activities along with hemispheric asymmetry and connectivity. To cover the ethical position theory, two different Likert scales was used in the study one is called Ethical Position Questionnaire (EPQ) with 20 items to be filled by leaders for ethical ideology and 2nd will be to measure ethical leadership 10 items to be filled by Peers and subordinates. Measuring the neurological factors influencing the leadership and moral self is difficult because EEG measuring instruments are required for this which could not measure in this research. It is recommended to replicate it with EEG measurement in future.